Penguatan ranah psikomotor mahasiswa dalam mengembangkan prototype produk/jasa melalui penerapan successive approximation model (SAM) - Arifah, Mir'atun Nur (Universitas Islam Indonesia, 2024)
This study aims to develop learning based on the Successive Approximation Model (SAM) in the Pengembangan Prototype Produk/Jasa course to strengthen students' psychomotor domain. The SAM approach is used to bridge the gap between theoretical mastery and practical application by involving iterative processes and collaboration with practitioners. The research adopts a development method with three main phases: the preparation phase, iterative design phase, and iterative development phase. Data were collected through observation, interviews, and documentation, then analyzed qualitatively. The findings indicate that the implementation of SAM enhances students' psychomotor skills. Students successfully developed prototypes of products/services relevant to Islamic Education, such as a Juz Amma application, collections of daily prayers, compilations of Hadith, and resources for sermons and lectures. Furthermore, practitioner involvement had a positive impact on students' understanding of workplace challenges and strengthened the connection between theory and application. The study concludes that SAM-based learning can effectively develop psychomotor skills while preparing students to meet workplace demands. The implementation of this model also enriches the learning experience by integrating cognitive, affective, and psychomotor aspects.